Ability of Immobilized Cyanobacteria to Remove Metal Ions From Solution and Demonstration of the Presence of Metallothionein Genes in Various Strains - J. L. Gardea-Torresdey; J. L. Arenas; N. M. C. Francisco; K. J. Tiemann; R. Webb (Journal of Hazardous Substance Research, 1998)
Synechococcus sp. PCC 7942 has the ability to grow in mass quantity under ideal conditions; such an ability provides usable biomass at a minimal effort. Using lyophilized biomass grown under normal conditions, Synechococcus was tested for its potential to bind metal ions from solution. Batch experiments have determined the optimum binding pH, time dependency, and metal binding capacities for copper(II), lead(II), nickel(II), cadmium(II), chromium(III), and chromium(VI), along with desorption of the metal bound. The biomass studied showed an affinity for five of the metal ions, with an optimum binding at pH 5. Time dependency studies showed that this cyanobacterium had rapid binding, while capacity experiments showed this cyanobacterial strain to bind 11.3 mg of copper(II) per gram of biomass, 30.4mg of lead(II) per gram of biomass, 3.2 mg of nickel(II) per gram of biomass, 7.2 mg of cadmium (II) per gram of biomass, and 5.4 mg of chromium (III) per gram of biomass. More than 98% of copper(II), lead(II), and nickel(II) metal ions were recovered, while over 50 % of cadmium(II) and chromium(III) were recovered when treated with 0.1M HCl. The biomass was immobilized in a silica polymer and tested for its binding ability under flow conditions. Using 0.1mM concentrations of the previously indicated metals, individual experimental results showed an average of 143 mg/L copper(II), 1456 mg/L lead(II), 142 mg/L nickel(II), and 529 mg/L cadmium(II) bound by the immobilized biomass. Treatment with 0.2M HCl resulted in nearly 100% recovery for both copper(II) and lead(II) from the column, 79% recovery of cadmium(II), while recovery for nickel(II) was 42%. Experiments were conducted to determine if many cycles of metal binding- stripping by the immobilized biomass were possible. Further, attempts were made to demonstrate the presence of metallothioneins in various strains of cyanobacteria which may serve as defense mechanisms against metal ion toxicity. Such proteins may be used to develop engineered strains of cyanobacteria with increased metal ion binding ability. Synechococcus can eventually be used as a source for a novel approach in using biosystems to remediate contaminants from solution and making those contaminants available to industry through an environmentally friendly biofiltration system.
Keywords: Synechococcus; cyanobacteria; heavy metal binding; bioremediation; metal recovery